Job Sheet Implementation as a Resource Mechanical Engineering Practice Learning at SMK Muhammadiyah 1 Sukoharjo - Mohammad Mughnil Labib; Budi Santosa; Edhy Susatya (Universitas Ahmad Dahlan, 2023)
This study aims to (1) analyze the use of job sheets as a source of practical learning in the Mechanical Engineering department, (2) identify constraints to using job sheets as a source of practical learning, (3) assess the extent to which job sheets increase student independence in practical learning, and (4) evaluate the improvement in students' skills resulting from using job sheets.This research is a qualitative study using a case study model. The study was conducted at SMK Muhammadiyah 1 Sukoharjo, with teacher and student respondents. Data was collected through interviews and analyzed using Miles and Hubberman's model analysis, which involves four steps: (1) data collection, (2) data reduction, (3) data presentation, and (4) drawing conclusions.The study results include an analysis of the use of job sheets as a learning resource, such as the job sheet making process, job sheet definitions, and job sheet implementation within the school curriculum. Constraints to using job sheets during practice were identified, such as the availability of facilities and infrastructure, students' knowledge of machines and equipment, reading and using measuring instruments, and damaged or erroneous machines or job sheets. The study also found an increase in student independence when using job sheets, including improved self-confidence, responsibility, high motivation, and reduced dependence on others. Finally, the study found an improvement in students' skills resulting from using job sheets, including increased knowledge and mastery of machines.